The Republic of Lithuania vs. the Belarus Nuclear Power Plant - Jakubowski, Jędrzej (Sensus Historiae, 2022)
The article presents the attitude of Lithuanian authorities toward the nuclear power plant in Ostrovets, Belarus. As early as the initial stage of the power plant’s construction, Lithuanian decision-makers opposed the project, raising arguments related to Belarus’ failure to comply with safety standards and international agreements. The Belarusian side hoped that Lithuania would be interested in purchasing electricity generated by BelAES, but since 2006, more interconnectors have been put into operation to connect Lithuania’s power grid with the synchronous systems of continental and northern Europe, providing alternative sources of energy. By being able to purchase it from directions other than Belarus and Russia, Lithuania has increased its energy security and was able to completely stop purchasing energy from Belarus in the fall of 2020, when the plant started to operate.